The causal effect of teen motherhood on worklessness - Ian Walker; Yu Zhu (University of Kent, School of Economics, 2009)
Teen motherhood continues to be high in the US and the UK relative to most other western European countries. While recent research has clarified how effective policies to reduce teen motherhood might be (Kearney (2009)), there remains little evidence that quantifies the causal effects of teen motherhood on such mothers and their first born children. This paper provides estimates of the causal effect of teen motherhood on worklessness and does so by exploiting the availability of two sources of exogenous variation in maternal age at first birth, which have not previously been used in this literature. Despite the strength of our instruments, we find no significant causal effects.
Keywords: I3; J13; 330; teen motherhood; worklessness; causal effect; Schwangerschaft; Jugendliche; Arbeitslosigkeit; Großbritannien; USA